Comparison of prevalence of intestinal parasitic infections in school children in Kuala Lumpur - Abdulla, Mahmood Ameen; Abdullah, Khairul Anuar; Sidik, Khalifah; Ismail, Salmah; Rahman, Suzainur Kulop Abdul; Mahziz, Mohammad Nazmul Hassan; Hamzah, Irwan (Faculty of Medicine, University of Malaya, 2002)
A comparative study was carried out to identify the prevalence of intestinal parasitic infestation among students in 3 different types of primary school1ocaled in Ampang area, Kuala Lumpur. A survey of infection rate was done from April 10 June 2001. Stool samples were randomly collected from one'hundred and eleven schoolchildren aged 9-12 years were examined for intestinal parasites, using a light microscope (or direct smear and after concentration for formol.-either method. It was found that an overall prevalence of intestinal parasite infection of schoolchildren was 51%. The infection rate of males and females was (60.3''1) and (29.20/0) respectively. Prevalence seems to be higher in the younger age groups. Also, the usual intestinal parasites were found more commonly in local and foreign schools than international schooL The local school had the highest prevalence (62%1), followed by the foreign school (52%) and international school (38.90/0). The prevalence in the international school was much lower compared to the local and foreign schools.